1994
DOI: 10.1007/bf00010106
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extraction of soil phytoavailable cadmium, copper, and lead by chelating resin membrane

Abstract: Cadmium, copper, and lead were extracted from suspensions of contaminated soils using metal chelating exchange resin membranes. Nine soils with widely varying properties and Cd, Cu and Pb levels were tested. Soil suspensions made up with 4 g in 40 mL deionized water were equilibrated with 5 cm 2 Ca-saturated Chelex exchange resin membrane which was retained inside a polypropylene bag and shaken at 150 rpm for 24 hrs. Resin membrane extractable Cd, Cu and Pb of the soils were correlated with Cd, Cu, and Pb upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Several experiments such as the ion exchange resins have used for determination of free ion and different species of metals in soil solution [17]. Khoshgftarmanesh et al (2006) found significant correlation relationship between MINTEQA2 model and Amberlite resin to estimate soluble concentrations of the Cd 2+ and Zn 2+ ions in soil [4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several experiments such as the ion exchange resins have used for determination of free ion and different species of metals in soil solution [17]. Khoshgftarmanesh et al (2006) found significant correlation relationship between MINTEQA2 model and Amberlite resin to estimate soluble concentrations of the Cd 2+ and Zn 2+ ions in soil [4].…”
Section: Introductionmentioning
confidence: 99%
“…Khoshgftarmanesh et al (2006) found significant correlation relationship between MINTEQA2 model and Amberlite resin to estimate soluble concentrations of the Cd 2+ and Zn 2+ ions in soil [4]. Significant relationship between the Amberlite resin and MINTEQA2 calculated free Zn 2+ and Cd 2+ showed that the MINTEQA2 model is appropriate for estimation of soluble Zn 2+ and Cd 2+ [17]. The resins can also be used for extraction of available metal pools in soil [17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations